Resilience of nitrification process in agricultural and restored soils of central Argentina - Romero, Carlos Matías (2013)
Fil: Romero, Carlos Matías. Universidad Nacional de Córdoba. Facultad de Ciencias Agropecuarias. Cátedra de Microbiología Agrícola; Argentina.